Environmental determinants of leaf litter ant community composition along an elevational gradient. (7th October 2020) - Fichaux, Mélanie; Vleminckx, Jason; Courtois, Elodie A.; H. C. Delabie, Jacques; Galli, Jordan; Tao, Shengli; Labrière, Nicolas; Chave, Jérôme; Baraloto, Christopher; Orivel, Jérôme
Abstract: Ant communities are extremely diverse and provide a wide variety of ecological functions in tropical forests. Here, we investigated the abiotic factors driving ant composition turnover across an elevational gradient at Mont Itoupé, French Guiana. Mont Itoupé is an isolated mountain whose top is covered by cloud forests, a biogeographical rarity that is likely to be threatened according to climate change scenarios in the region. We examined the influence of six soil, climatic, and LiDAR‐derived vegetation structural variables on leaf litter ant assembly (267 species) across nine 0.12‐ha plots disposed at three elevations (ca. 400, 600, and 800m asl). We tested (a) whether species cooccurring within a same plot or a same elevation were more similar in terms of taxonomic, functional, and phylogenetic composition, than species from different plots/elevations, and (b) which environmental variables significantly explained compositional turnover among plots. We found that the distribution of species and traits of ant communities along the elevational gradient was significantly explained by a turnover of environmental conditions, particularly in soil phosphorus and sand content, canopy height, and mean annual relative humidity of soil. Our results shed light on the role exerted by environmental filtering in shaping ant community assembly in tropical forests. Identifying the environmental determinants of ant species distribution along tropical elevational gradients could help predicting the future impacts of global warming on biodiversity organization in vulnerable environments such as cloud forests.